Effect of drying parameters and geometry on papaya quality - Md. Zaki, Nurul Asyikin; Mohd. Darwi, Lizawati; Md. Salleh, Liza; Muhamad, Ida Idayu (2005)
Due to the importance of minimizing thermal stresses over drying and maintenance of relevant compounds, selection of proper drying condition is necessary to maintain the quality of the processed fruit. The aim of this project is to study the effect of various drying parameters i.e. temperature, air velocity and geometry cut on the quality of papaya based on moisture content. Slices (0.5 x 1.5 x 1.5 cm) and cubes (1.0 cm) of papaya were treated in tray drier (Armfield UOP8) at different levels of temperature (40, 50 and 60C) and air velocity (0.5, 1.0 and 1.5 m/s). Temperature was found to be significantly influencing the drying performance for both slices and cubes. However, geometry was the most significant factor played as a controlling effect on moisture content, in which larger surface exposure helps temperature to take action strongly. Slices suffered higher water loss than cubes with regression level (R2) 0.932.